Imprinting of IgA responses in previously infected individuals receiving bivalent mRNA vaccines (WT and BA.4/BA.5 or WT and BA.1) - Goh, Yun Shan (2024)
Objectives: The emergence of new SARS-CoV-2 variants has led to the development of Omicron-targeting bivalent mRNA vaccines. It is crucial to understand how bivalent vaccines may improve antibody responses against new variants. Methods: A total of 107 participants, who had three COVID-19 WT mRNA vaccine doses, were recruited, and given either a monovalent (WT) or a bivalent mRNA vaccination (Pfizer/BioNTech Bivalent (WT and BA.4/BA.5) or Moderna Bivalent (WT and BA.1). Blood samples were taken before booster and at 28 days post-booster. Results: We found significantly lower fold change in serum binding IgA responses against BA.1, BA.5 and EG.5.1 spike in the bivalent booster group, compared with the monovalent (WT) booster group, following vaccination. However, this was only observed in individuals with prior infection. The relative fold change in serum binding IgA response was more skewed towards WT over variant (BA.1, BA.5 or EG.5.1) spike in previously infected bivalent-booster-vaccinees, as compared with previously infected monovalent-(WT)-booster-vaccinees. Conclusion: The findings suggest imprinting of antibody responses that is shaped by the first vaccination (WT spike). Previous infection also affects the boosting effect of follow-up vaccination. Studies are needed to understand how to induce a robust and long-lasting IgA immunity for protection against COVID-19 infection.